PENGARUH KONTEN MARKETING INFLUENCER TIKTOK @fadiljaidi TERHADAP MINAT BELI GENERASI Z PADA PRODUK PARFUM SCARLETT - Syahla Nabilatun Nisa; Fauzi Syarief (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of TikTok influencer @fadiljaidi's marketing content, comprising content originality, content quality, emotional appeal, and content quantity, on Generation Z's purchase intention toward Scarlett perfume products. This research employs a quantitative approach with an explanatory research design through a survey method. Data were collected from 100 respondents who are active TikTok users among Generation Z, followers of the @fadiljaidi account, and had previously seen promotional content for Scarlett perfume, using a purposive sampling technique. Data were analyzed using multiple linear regression with SPSS version 25. The results show that the four content marketing variables simultaneously have a positive and significant effect on Generation Z's purchase intention (F count = 16.963; Sig. = 0.000), contributing 39.2% (Adjusted R Square). Partially, content originality and content quality are proven to have a positive and significant effect on purchase intention, with content quality being the most dominant variable. Emotional appeal has no significant effect, while content quantity has a significant but negative effect, indicating a content fatigue phenomenon. This study recommends that perfume content marketing strategies should focus more on originality and quality of content with a proportional posting frequency.